OPTIMUM PROSESSENTRERING - Adendorff, K. (The South African Journal of Industrial Engineering, 2012)
ENGLISH ABSTRACT: The paper derives an expression for optimum process centreing for a given design specification and spoilage and/or rework costs. AFRIKAANSE OPSOMMING: Die problem Van prosessentrering vir n gegewe ontwerpspesifikasie en herwerk- en/of skrootkoste word behandel.